A Novel Minimally Invasive Spherical Periacetabular Osteotomy: Pelvic Ring Preservation and Patient-Specific Osteotomy by Preoperative 3-Dimensional Templating. (15th September 2021) - Kaneuji, Ayumi; Hara, Toshihiko; Takahashi, Eiji; Fukui, Kiyokazu; Ichiseki, Toru; Kawahara, Norio
Abstract : Background: Spherical periacetabular osteotomy (SPO) is a novel osteotomy involving splitting the teardrop, using patient-specific preoperative planning, and requiring only a 7-cm skin incision. We report preoperative planning methods and short-term results of SPO. Methods: In preoperative planning, computed tomography (CT) images were imported into 3-dimensional templating software. The radius of the curved chisel was mapped to pass through the teardrop, the infracotyloid groove of the ischium, and the area between the anterior superior iliac spine and the anterior inferior iliac spine. The osteotomy height and the predicted depth of osteotome insertion were measured, and those values were reproduced during surgery. We performed a retrospective analysis of data on 52 consecutive patients (55 hips) with hip dysplasia who underwent SPO and were followed for at least 2 years: 27 hips had Tönnis grade 0, 21 had grade 1, and 7 had grade 2. The mean age at surgery was 38 years (range, 17 to 56 years). The rotated bone fragment and iliac crest were fixed with absorbable screws. Statistical analysis was performed with the paired t test. Results: The mean (range) of the lateral center-edge and sourcil angles were 6.0° (−20° to 18°) and 26.0 (13° to 38°), respectively, before surgery and 30.0° (15° to 43°) and 3.8° (−4° to 27°), respectively, after surgery (p < 0.001). However, 11 hips (20%) showed a loss of correction of bone rotation (<3 mm) or the sourcil angle (<3°). Radiographs showed bone union in all hips within 3 months after the surgery. Early second surgery related to absorbable screws was performed in 2 hips. No patient had required conversion to total hip arthroplasty at the time of writing. Clinical scores were significantly improved at the 2-year follow-up (p < 0.001). Paresthesia of the lateral femoral cutaneous nerve area was very common but had resolved in 92% of the patients at the 2-year follow-up. Conclusions: SPO is a novel minimally invasive periacetabular osteotomy that has the potential disadvantage of early loss of correction (observed in 20% of the hips in the present study) but may provide the benefit of decreasing the risk of nonunion at the pubis osteotomy site. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.